SP0131 Fibromyalgia: What is New. (9th June 2015) - Crofford, L.J.
Abstract : Further clarification of the impact of FM classification criteria has emerged with a higher prevalence and greater proportion of men identified with the modified 2010 criteria. This together with ongoing epidemiologic studies has confirmed the relationships between FM, other pain conditions, and mood disorders. Advances in the understanding of FM physiology have continued to evolve with advanced neuroimaging studies confirming altered central representation of pain as well as more static changes in brain volumes and brain region connectivity. Additional studies reveal alterations in brain function during cognitive processing. In addition to these advances, there has been re-focused attention on peripheral mechanisms that may initiate or maintain centrally amplified pain, specifically focusing on evidence for involvement of cytokines, oxidative stress and mitochondrial dysfunction, and small fiber neuropathy. The potential role of autonomic dysfunction as a unifying factor in these peripheral changes continues to be investigated. Few advances were made in treatments for FM with most studies re-confirming the limited effectiveness of available pharmacologic treatments and re-affirming the utility of non-pharmacologic treatment modalities. The search for novel approaches to treatment may be informed by studies of the physiology of FM. Disclosure of Interest: None declared